2006
DOI: 10.1074/jbc.m511525200
|View full text |Cite
|
Sign up to set email alerts
|

Defective Human Leukocyte Antigen Class I-associated Antigen Presentation Caused by a Novel β2-Microglobulin Loss-of-function in Melanoma Cells

Abstract: The major histocompatibility complex class I molecules consist of three subunits, the 45-kDa heavy chain, the 12-kDa ␤ 2 -microglobulin (␤ 2 m), and an ϳ8 -9-residue antigenic peptide. Without ␤ 2 m, the major histocompatibility complex class I molecules cannot assemble, thereby abolishing their transport to the cell membrane and the subsequent recognition by antigen-specific T cells. The human leukocyte antigen (HLA) 4 class I molecules, encoded by the genes located in the major histocompatibility complex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 30 publications
0
47
1
Order By: Relevance
“…In this regard, Lehmann et al (51) demonstrated that the TAs recognized by the CTLs isolated from recurrent melanoma metastases were different from those recognized by the CTLs isolated from autologous primary lesions. In addition, some of us (14) have shown a shifting of CTL specificity from HLA-A2-MART-1 [27][28][29][30][31][32][33][34][35] complexes to HLA-A2-Tyr 369 -377 complexes in two sequential melanoma metastases with distinct HLA class I abnormalities caused by a mutant ␤ 2 m protein (32). These results are consistent with the possibility that the specificity of a patient's immune response can change in response to changes in the expression of targets by melanoma cells, which have developed immunoescape mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Lehmann et al (51) demonstrated that the TAs recognized by the CTLs isolated from recurrent melanoma metastases were different from those recognized by the CTLs isolated from autologous primary lesions. In addition, some of us (14) have shown a shifting of CTL specificity from HLA-A2-MART-1 [27][28][29][30][31][32][33][34][35] complexes to HLA-A2-Tyr 369 -377 complexes in two sequential melanoma metastases with distinct HLA class I abnormalities caused by a mutant ␤ 2 m protein (32). These results are consistent with the possibility that the specificity of a patient's immune response can change in response to changes in the expression of targets by melanoma cells, which have developed immunoescape mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were allowed to expand for 3 weeks and then harvested when necessary. The specificity of CTLs was assessed by their cytotoxicity of HLA-A3-transfected HEK293 cells (4 ϫ 10 6 cells/ml) pulsed with gp100 [17][18][19][20][21][22][23][24][25] peptide (400 g/ml) versus those pulsed with irrelevant HLA-A3-binding CSPG4 495-503 peptide (TLLDVVNRK, 400 g/ml) using a standard 4-h 51 Cr-release assay (32). These CTLs were then assayed for their ability to recognize and lyse mock-and tapasin-transfected COPA-159 cells treated with IFN-␥, 5AdC, or their combinations.…”
Section: Methylation-specific Pcr (Msp)mentioning
confidence: 99%
“…In addition, restoration of TAP activity by transfection of tumor cells enhances class I mediated antigen presentation and induces susceptibility to CTL killing, both in vitro and in vivo [1,23]. In contrast, IFN-γ and TNF-α treatment failed to elicit class I expression in some class I deficient tumors which are associated with a defective β 2 m gene [5] or DNA hypermethylation [40]. However, mutation of β 2 m pis not a common mechanism of class I deficiency in tumors [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Immune escape by virally-infected and tumor cells has been correlated with down-regulation of antigen-presenting molecules [66,67].…”
Section: Direct-acting Effectsmentioning
confidence: 99%